Exclusive Breastfeeding for Twin Babies and Its Influencing Factors: A Study in East Java, Indonesia. (29th March 2019) - Anjarwati, Nurul; Waluyanti, Fajar Tri; Rachmawati, Imami Nur
ABSTRACT: This study aimed to identify the factors that influence the success of exclusive breastfeeding in twins. This cross-sectional study was conducted on 184 mothers who had twins aged 6–23 months in Malang Raya, East Java, Indonesia and used the consecutive sampling technique. The data was collected through distributing questionnaires containing questions related to knowledge about exclusive breastfeeding, breastfeeding self-efficacy, and the support of family and certified health workers. Multinomial regression statistical test results show that the most influential factor for the success of exclusive breastfeeding with twins was breastfeeding self-efficacy (OR 0.111; 95% CI 0.033–0.387). A high level of breastfeeding self-efficacy can increase a mother's confidence to be able to provide exclusive breastfeeding for twins. This study suggests that nurses can provide breastfeeding counselling to improve breastfeeding self-efficacy.